Comparative Investigation of Rheological Characteristics of the Original Drug Triderm and Its Generics in the Form of Cream - E. I. Molokhova; YU. V. Sorokina (Антибиотики и Химиотерапия)
Rheological properties of mild pharmaceutical formulations (creams) with glucocorticosteroids, such as Triderm (Belgium), Akriderm GK (Russia) and Kanizon plus (India) were studied. The study revealed differences in the structural-strength properties of the medicines (viscosity, critical shear stress). The necessity of rheological investigations during development of generic medicines was shown.